2010
DOI: 10.1016/j.jtcvs.2009.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Cold blood cardioplegia reduces the increase in cardiac enzyme levels compared with cold crystalloid cardioplegia in patients undergoing aortic valve replacement for isolated aortic stenosis

Abstract: Antegrade cold blood cardioplegia provides better myocardial protection than cold crystalloid cardioplegia in patients undergoing aortic valve replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 24 publications
1
31
1
Order By: Relevance
“…In literature there are little data comparing warm blood and CCC in the aortic valve replacement surgery. Braathen and Tønnessen in 80 patients undergoing isolated aortic valve replacement showed a better myocardial protection with the use of cold blood cardioplegia in comparison with CCC (20). In contrast to the observed value of CK-MB in our study that was less than 20 ng/mL at 24 PO hours in the CCC group, they found a CK-MB value greater than 45 micrograms (mcg)/L at 20 PO hours with the use of the CCC.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…In literature there are little data comparing warm blood and CCC in the aortic valve replacement surgery. Braathen and Tønnessen in 80 patients undergoing isolated aortic valve replacement showed a better myocardial protection with the use of cold blood cardioplegia in comparison with CCC (20). In contrast to the observed value of CK-MB in our study that was less than 20 ng/mL at 24 PO hours in the CCC group, they found a CK-MB value greater than 45 micrograms (mcg)/L at 20 PO hours with the use of the CCC.…”
Section: Discussioncontrasting
confidence: 94%
“…Interestingly, the mean value of cTnI at 24 and 48 hours reported using cold and WBC was similar to that observed in our study in the CCC group and in the WBC group, respectively. However, although the reported study and other studies have underlined some different degree of myocardial protection in favor of one or of the another type of cardioplegia, no differences have been observed in terms of perioperative myocardial infarction, low output cardiac syndrome, PO non-cardiac major complications, and death (12,(20)(21)(22)(23). These findings are in accordance with those observed in our study: in fact, although the release of cardiac enzymes was in favor of CCC, the perioperative outcome was similar in both groups of patients.…”
Section: Discussionmentioning
confidence: 64%
“…These mean postprocedural cardiac marker levels are comparable with those reported after TAVI (with transfemoral and transapical approach) with the Edwards SAPIEN (Edwards Lifesciences Inc; Irvine, CA) device. 32 The values of postprocedural markers are remarkably low compared with those found after surgical valve replacement and CABG 14,19,20,33,34 and higher compared with those after PCI. 9,12,15,17,18 The absence of aortic cross-clamping and cardioplegia in combination with less direct myocardial trauma could explain the relatively lower biomarker levels after TAVI compared with cardiac surgery.…”
Section: Discussionmentioning
confidence: 97%
“…Histidine has a buffer effect and may enhance the efficiency of anaerobic glycolysis, tryptophane stabilizes the cell membrane and the addition of mannitol decreases cellular oedema, whereas ketoglutarate is a precursor of nicotinamide adenine dinucleotide (6). Several studies have demonstrated the efficacy of the HTK solution based on biochemical markers or physiological evaluation in experimental models (7)(8)(9). HTK solution helps to preserve myocardial adenosine triphosphate stores, improve post-arrest contractile function and minimize myocardial necrosis (10,11).…”
Section: Introductionmentioning
confidence: 99%